Effect of Bacterial Lipopolysaccharide Contamination on Gutta Percha- versus Resilon-Induced Human Monocyte Cell Line Toxicity. - Jamshid Hadjati; Hadi Assadian; Abdollah Ghorbanzadeh; Maryam Nourizadeh; Tahereh Fattah; Noushin Shokouhinejad (Tehran University of Medical Sciences, 2015)
Cytotoxic effects of obturation materials were tested in presence and absence of endotoxin on human monocytes in vitro.Human monocytes from THP-1 cell line were cultured. Three millimeters from the tip of each Resilon and gutta percha points were cut and directly placed at the bottom of the culture wells. Cultured cells were exposed to gutta percha (groups G1 and G2) and Resilon (R1 and R2). Ten μg/ml bacterial lipopolysaccharide (LPS) was added to the culture wells in groups G1 and R1. Positive control included the bacterial LPS without the root canal filling material and the negative control contained the cells in culture medium only. Viability of cells was tested in all groups after 24, 48, and 72 hours using the methylthiazolyldiphenyl-tetrazolium bromide (MTT) assay for at least 3 times to obtain reproducible results. Optical density values were read and the data were analyzed using three-way ANOVA and post hoc statistical test.The results showed that cells in G2 had the lowest rate of viability at 24 hours, but the lowest rate of viable cells was recorded in G1 at 48 and 72 hours. The effect of LPS treatment was not statistically significant. Resilon groups showed cell viability values higher than those of gutta percha groups, although statistically non-significant (P=0.105). Cell viability values were lower in gutta percha than Resilon groups when LPS-treated and LPS-untreated groups were compared independently at each time point.It could be concluded that none of the tested root canal filling materials had toxic effects on cultured human monocyte cells whether in presence or absence of LPS contamination.